Sistem Pendukung Keputusan Evaluasi Pemilihan Pemenang Pengadaan Aset dengan Metode Simple Additive Weighting (SAW) - Nugraha, Fajar; Surarso, Bayu; Noranita, Beta (JSINBIS (Jurnal Sistem Informasi Bisnis), 2012)
Procurement of assets by auction requires a decision support in selecting the winning bidder so that decision makers can pick and choose the winner of the auction. This study aims to develop a Decision Support System (DSS), which serves as an aid in decision mak ing in the process  of  evaluating  the  winning  bidder  acquisitions.  In order to  achieve  the  purpose  of  SPK  well  then helped  by  using  one  of  the methods in decision-making that is the method of Simple Additive weighting method (SAW) to evaluate alternatives in the provision of asset  based  decision-making  criteria.  This  method  has  the  advantage  criteria  (benefits)  and  cost  criteria  (cost).  Criteria  advantage (benefit) is used when considering the aspects of decision making maximum profit. While the cost criteria (cost) is the inver se of the attributes of an advantage, in this draft decision will be looking  for a minimal fee. The results may support the decision on the selection of an alternative evaluation of acquisitions winners based on predetermined criteria.Keywords: Acquisitions; Decision support systems; Simple additive weighting